2004
DOI: 10.1152/japplphysiol.00444.2003
|View full text |Cite
|
Sign up to set email alerts
|

Age dependency of cardiovascular autonomic responses to head-up tilt in healthy subjects

Abstract: In elderly subjects, heart rate responses to postural change are attenuated, whereas their vascular responses are augmented. Altered strategy in maintaining blood pressure homeostasis during upright position may result from various cardiovascular changes, including age-related cardiovascular autonomic dysfunction. This exploratory study was conducted to evaluate impact of age on cardiovascular autonomic responses to head-up tilt (HUT) in healthy subjects covering a wide age range. The study population consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
113
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 58 publications
21
113
1
5
Order By: Relevance
“…This may reflect age-related attenuation of NO production and cardiovascular autonomic function (35). The lack of response on MVR in the diabetic patients in the present study might also be due to even more pronounced cardiovascular autonomic alterations compared with the middle-aged control subjects.…”
Section: Discussionmentioning
confidence: 58%
“…This may reflect age-related attenuation of NO production and cardiovascular autonomic function (35). The lack of response on MVR in the diabetic patients in the present study might also be due to even more pronounced cardiovascular autonomic alterations compared with the middle-aged control subjects.…”
Section: Discussionmentioning
confidence: 58%
“…Earlier studies described an increase of SAP mean [7,48] and SAP variability with aging [10][11][12][49][50][51]. These results have been interpreted as a consequence of the increase of sympathetic activity and/or modulation directed to the vessels with age [48].…”
Section: Complexity Of the Sap Variability At Rest: Aging And Gender mentioning
confidence: 83%
“…These results have been interpreted as a consequence of the increase of sympathetic activity and/or modulation directed to the vessels with age [48]. However, a modified cardiac reserve [7], changes of the structure of the arteries (i.e., increased stiffness, decreased compliance, and endothelial dysfunction) [52], and changes of diastolic filling and increases in collagen in the left ventricle might play a role in the modification of SAP mean and variance with age [7,31].…”
Section: Complexity Of the Sap Variability At Rest: Aging And Gender mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of men and women from 23-77 yr of age indicated that the heart rate response to tilt was reduced with aging, but vascular responses appeared to be enhanced to protect against low blood pressure (17,32). A study that focused on postmenopausal women also reported a reduction in arterial baroreflex responsiveness and heart rate control characterized by greater sympathetic and reduced parasympathetic modulation (33).…”
mentioning
confidence: 99%